Impact of fertilizers on chemical analysis, amino acid and fatty acid compositionof Sudanese soybean genotype - Ahmed, Wjdan M. (Array, 2018)
The impact of fertilizer on chemical analysis, amino acid and fatty acid composition of soybean (Glycine max L merril) Sudanese local genotype was studied. A field experiment was conducted for two consecutive seasons (2009-2010 and 2010-2011) on the demonstration farm of the College of Agricultural studies, Sudan University of Science and Technology at Shambat. The experiment was laid out in a randomized complete block design with four replicates. The fertilizer treatments consisted of three types: Urea (180 kg/ha), NP (361kg/ha), compost (1904.76 kg/ha) and then control. The results showed that fertilizer treatments had no significant difference in proximate analysis of soybean seeds except in fibber. In fatty acid, control and nitrogen treatments gave the highest percentage of palmitic acid. NP and compost gave highest effect in linoleic acid and compost gave highest effect in polyunsaturated fatty acids. As general compost treatment gave the lowest effect in all amino acids and the highest effect in minerals. Control gave the highest effect in all amino acids. The application of nitrogen, NP and compost fertilizers for soybean significantly increased number of seeds/plant, weight of seeds\plant and seeds yield. The results also showed that urea fertilizer increased protein and ash content, while NP increased oil and carbohydrate contents. Compost increased all the minerals, but there was no effect on fatty and amino acid composition.